The usage of communication technology among students / Muhammad Nur Syahib Zahari and Mohamad Hafiz Harun - Zahari, Muhammad Nur Syahib; Harun, Mohamad Hafiz (2013)
The aim of the study is to examine the usage of the communication technology among students. We are focusing on the academic performance of the respondents. The sample sizes of this study are students from Kolej Sentral and UiTM Jengka, Pahang. 60 questionnaires were distributed but only 50 were useful for further analysis. The results showed a positive relationship between the communication technology and academic performance. The result was consisted with previous studies that also indicated a positive result between communication technology and academic performance.